OPTIMALISASI KINERJA JARINGAN VPN DENGAN METODE DMVPN - Juliansah, Jodi; Akbar, Yuma (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
DMVPN (Dynamic Multipoint Virtual Private Network) is a VPN technology that can simplify the configuration process and improve network efficiency. The purpose of this research was conducted as a response to the obstacles experienced by companies in VPN network performance that did not meet expectations and reduced high operational and infrastructure costs related to the performance of the current VPN network. In addition, to determine the extent to which the use of DMVPN can improve the performance of VPN networks in companies. The method used is data collection through observation and interviews, and analysis of the data that has been collected. The results showed that the use of DMVPN can increase the efficiency of the VPN network in the company by reducing traffic load and speeding up the data transmission process. Therefore, DMVPN technology is highly recommended for companies that require complex VPN networks and need optimal network performance. The results of this research are expected to provide a better understanding of the potential and effectiveness of using DMVPN in optimizing the performance of VPN networks in companies. It is expected that the implementation of DMVPN can increase data transfer speed, reduce latency, and increase data security in VPN networks. In addition, it is also expected that the use of DMVPN can reduce the operational and infrastructure costs associated with VPN networks, so that companies can achieve higher efficiency